The effect of long-term use on the Catch efficiency of Biodegradable gillnets - Grimaldo, Eduardo; Herrmann, Bent; Jacques, Nadine; Kubowicz, Stephan; Cerbule, Kristine; Su, Biao; Larsen, Roger B.; Vollstad, Jørgen (Marine Pollution Bulletin, 2020)
The effect of long-term use on the catch efficiency of biodegradable gillnets was investigated during commercial fishing trials and in controlled lab aging tests. The relative catch efficiency between biodegradable and nylon gillnets was evaluated over three consecutive fishing seasons for Atlantic cod (Gadus morhua) in Norway. The biodegradable gillnets progressively lost catch efficiency over time, as they caught 18.4%, 40.2%, and 47.4% fewer fish than the nylon gillnets during the first, second, and third season, respectively. A 1000-hour aging test revealed that both materials began to degrade after just 200 h and that biodegradable gillnets degraded faster than the nylon gillnets. Infrared spectroscopy revealed that the chemical structure of the biodegradable polymer changed more than the nylon. Although less catch efficient than nylon gillnets, biodegradable gillnets have great potential for reducing both capture in lost fishing gear and plastic pollution at sea, which are major problems in fisheries worldwide.